Environmental behaviors of students attending school of medicine, Maltepe University and confounding factors - (:unkn) unknown (My University, 2011)
Introduction And Purpose Environmental environment is defined as "a human notices significance of his/her relation with the environment in terms of his/her existence". In the society, several professional groups are of extreme importance for increasing awareness of subjects and leading to behavior changes. Environmental behaviors of physicians having substantial effects on public health and education are important for social awareness. This study is conducted in order to assess environmental behaviors of students attending school of medicine, Maltepe University. Material and Method: This study is a cross-sectional trial which was conducted on Grade 1-6 students attending School of Medicine, Maltepe University. All students (n = 167) were enrolled into the study and 147 students (88,02%) could be reached due to various reasons. In this study conducted for determining environmental behaviors of students in relation with environmental awareness, the Environmental Behavior Sub-scale of "Environmental Attitude Scale" developed by Uzun and Saǧlam (2006). The estimated reliability coefficients of Environmental Behavior Sub-scale are _=0.88 ve 0.81 (Spearman Brown two-halves test correlation) (Uzun and Saǧlam, 2006). In the "Environment Behavior Sub-scale", those items were scaled in five categories including "Always", "Mostly", "Occasionally", "Rarely" and "Never". When scores given by all students were sum for each statement, the group score on relevant issue was determined and a view was obtained on awareness of the group. Data entry process of the study was conducted using SPSS version 11.5 software package and statistical assessment included t-test and ANOVA. Results: Of all students, 51.0% were female and 49.0% were male and 44.2% could drive motor vehicle (motorcycle and automobile).The option of "always" was marked by 17.7% of the participants to the question "I watch TV and radio shows on the environment", by 12.2% to the question "I follow environmental events from newspapers", by 10.9% to the question "I watch documentaries on the environment", by 19.0% to the question "I read books, other than text books, about the environment", by 17.7 to the question "I follow popular journals about the environment", by 26.5% to the question "I follow scientific articles on the environment", by 10.9% to the question "I do not hesitate to warn anybody who damages the environment" and by 17.0% to the question "I would like to voluntarily participate to any activity about environmental cleaning". The option "Never" was preferred by 14.3% to the question "My friends recognizes my environment-friendly view", by 6.8% to the question "I may work free of charge for a habitable environment", by 6.1% to the question "I share my knowledge about the environment with my friends" and by 7.5 to the question "I act carefully when I buy a product that the waste is recyclable". A significant difference was not found in Environmental Behavior Scale scores of students based on age, gender, the location where student lives, monthly allowance, education status of mother, education status of father, mean income level of the family, the longest residence location, ability to drive motor vehicle, regular sports activities, regular use of alcohol and smoking status. Conclusion and Advices: The environmental awareness of students attending the school of medicine will somehow influence the healthcare service provided by them and this awareness will provide them the necessary equipment to pioneer the society they will serve. © SGEM2011 All Rights Reserved by the International Multidisciplinary Scientific GeoConference SGEM.
Keywords: Environment; Environmental Behavior sub-scale; Students of School of Medicine